(untitled) (Conferencea, 2025)
This article, based on etymological analysis, examines approaches to developing students’ logical thinking skills. The approaches analyzed were value, social, cognitive, and functional approaches. Value approach - it is explained that from the moment of the emergence of human society, language develops, polishes and is enriched by it and that at some point it changes its form, but never changes its character and function. The article also mentions the importance of the social approach - increasing the attention of individuals to language in society, increasing the culture of communication between them.